Exome sequencing and genome-wide copy number variant mapping reveal novel associations with sensorineural hereditary hearing loss - Haraksingh, Rajini R (BMC Genomics, 2014)
BACKGROUND: The genetic diversity of loci and mutations underlying hereditary hearing loss is an active area of investigation. To identify loci associated with predominantly non-syndromic sensorineural hearing loss, we performed exome sequencing of families and of single probands, as well as copy number variation (CNV) mapping in a case–control cohort. RESULTS: Analysis of three distinct families revealed several candidate loci in two families and a single strong candidate gene, MYH7B, for hearing loss in one family. MYH7B encodes a Type II myosin, consistent with a role for cytoskeletal proteins in hearing. High-resolution genome-wide CNV analysis of 150 cases and 157 controls revealed deletions in genes known to be involved in hearing (e.g. GJB6, OTOA, and STRC, encoding connexin 30, otoancorin, and stereocilin, respectively), supporting CNV contributions to hearing loss phenotypes. Additionally, a novel region on chromosome 16 containing part of the PDXDC1 gene was found to be frequently deleted in hearing loss patients (OR = 3.91, 95% CI: 1.62-9.40, p = 1.45 × 10(-7)). CONCLUSIONS: We conclude that many known as well as novel loci and distinct types of mutations not typically tested in clinical settings can contribute to the etiology of hearing loss. Our study also demonstrates the challenges of exome sequencing and genome-wide CNV mapping for direct clinical application, and illustrates the need for functional and clinical follow-up as well as curated open-access databases. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2164-15-1155) contains supplementary material, which is available to authorized users.